PERLINDUNGAN HUKUM TERHADAP JURNALIS DALAM MENULISKAN BERITA KEPADA MASYARAKAT SEBAGAI WUJUD KEBEBASAN BERPENDAPAT DAN KONTROL SOSIAL DITINJAU DARI UU PERS DAN UU ITE (Studi Kasus: 46/Pid.Sus/2021/PN.Plp.) - Vina Octavia; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
Freedom of the press is one manifestation of the mandate of Article 28F of the 1945 Constitution of the Republic of Indonesia which reflects the freedom to use various media in terms of seeking, obtaining, possessing, storing, processing and conveying information. In carrying out its functions, rights, obligations and roles, the press respects human rights, and must be professional and controlled by the community. Today, there is a phenomenon of press criminalization caused by journalistic products reported by parties who feel aggrieved. The research method used is normative juridical research. The results of this study are that legal protection for the press as a social institution and vehicle for mass communication that has freedom of expression and independence has been explicitly and surely accommodated in Article 8 of the Press Law. However, often this legal protection does not work as it should in social life. Journalistic products produced by the press and press companies should not be criminalized or brought into the realm of crime. Therefore, it is necessary to re-enforce the mechanism regarding settlements related to the press and adjustments to the Press Law and ITE Law must be made.